LA ORGANIZACIÓN COMUNAL EN EL DISTRITO DE ZARAGOZA EN PALMARES. EL SURGIMIENTO DE LA ASOCIACIÓN DE DESARROLLO INTEGRAL EN LA DÉCADA DE 1970 - Rodríguez Sancho, Javier (Universidad de Costa Rica, 2021)
This article examines the historical performance of community organizations, specifically the Integral Development Association in Zaragoza, Palmares, in terms of its conflicts and its internal necessities since the decade of 1970. For this analysis, primary sources such as institutional records, scientific studies and data were used. In addition, the article highlights the role of public authorities, the political and institutional control, and their agreements to deal with daily-life aspects in this community and others in the Western Region of Costa Rica during the second half of the 20th century.